Pengenalan Algoritma Dengan Menggunakan Permainan Squaring the Square di SMA 1 Batukliang Utara Lombok Tengah - Siboro, Ayes Malona; Wahidah, Fathul Maulina; Putra, Lalu Riski Wirendra; Lestari, Sahin Two; Putri, Syaftirridho; Pratama, Rendi Bahtiar; Wardhana, I Gede Adhitya Wisnu; Haryati, Ida (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2024)
This study aims to evaluate the application of the Squaring Square method in improving the understanding of algorithms, geometry and changes in students' attitudes towards mathematics at SMA Negeri 1 Batukliang Utara, Central Lombok. This method involves practical activities in which students compose several small squares into one large square shape, designed to hone spatial skills and problem-solving abilities. Data analysis from the pre-test and post-test showed that applying this method significantly improved students' understanding of geometry concepts and their attitudes towards mathematics lessons. These findings align with constructivist theory, which emphasises the importance of experiential learning and visualization in improving deep conceptual understanding and offers valuable insights for teaching mathematics in schools.